Provable secure mutual authentication protocol for RFID in the standard model - Feng XIAO; Ya-jian, ZHOU; Jing-xian ZHOU; Xin-xin NIU (Tongxin xuebao)
The security issue of RFID is becoming more and more serious,in order to protect the RFID's information security and privacy,a mutual authentication protocol for RFID based on HB protocol was proposed in the standard model.The security proofs for this novel protocol was given by using the reduction method,and attacker's hardness was reduced to the indistinguishability between pseudo-random function and real random function.The implementation of proposed protocol only required lightweight pseudo-random generator and vector dot product operation and provided higher security and efficiency.The comparisons of security and performance were also given with other authentication protocols,the results show that the proposed protocol is feasible for RFID tags which are low cost and resource-constrained.